Has earnings inequality in Germany changed in the 1980's? - Viktor Steiner; Kersten Wagner (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
The development of the West German earnings distribution in the 1980's is analysed on the basis of both the German Socio-Economic Panel and micro-data from the Employment Register of the Federal Labour Office. We find that earnings inequality in Germany has increased very little in the 1980's, if at all. It is shown ·that the marked increase in earnings inequality found in previous studies based on the register data is a statistical artifact related to a change in the coding of the earnings data. Our decomposition analysis based on estimated earnings functions reveals that the relative stability of the German earnings distribution in the 1980's has not resulted from large compensating changes in the composition of the labour force on the one hand, and changes in the returns to human capital on the other. While both of these components have changed little in the observation period, the former rather than the latter component has contributed to the small increase in earnings inequality observed in the register data. If anything, the earnings differential between skilled and unskilled workers has become smaller during the 1980's, while within-inequality has contributed very little to changes in inequality. Overall, the empirical results of this study seem compatible with an institutional explanation of the stability of the German earnings distribution.
Keywords: J31; J24; 330